KARAKTERISTIK FISIK KIMIA DAN ORGANOLEPTIK PERMEN JELLY DARI SARI BUAH SRIKAYA PADA VARIASI KONSENTRASI AGAR-AGAR - Hasyim,Abdul Rahim,Rostiati, Hasriyanti (AGROTEKBIS, 2015)
The objectives of this study was to determined the concentration of gelatin that of the best in the production of jelly candy from sugar apple juice were physical, chemical and organoleptic characteristics. This study used completely randomized design with using sugar apple juice concentration as treatment consists of 4 degree i.e.6, 8, 10 and 12% (w/w). The organoleptic test using a randomized block design classification was based on each panelist, then the number of them panelist were involved 15 people. each treatment was repeated two times, so that would be obtained 8 samples. The treatment is significant in a further test with honestly significant difference test level of 5%.The results showed that the physical quality of the gelatine concentrations differences to have total soluble solid. The highest content of it made from gelatine 8% that is 1,94%, the solubility 12% (7.70%) and the water holding capacity at the 6% (2.82%), oil holding capacity at the 6% (2.15%), chemical quality such as water content at the8% (62.46%), vitamin C 6% (33.00% ) and dietary fiber at the 12%(7.46%). While the best of organoleptic test concentrations of gelatine at the 8% i.e the texture 4.20, colours 5.40, flavour 4.27, taste 4.27 and alike of comprehenship 4.80 which the were included neutral.